Factors influencing the early development of world-class Caribbean track and field athletes: A qualitative investigation - Thomas, C. E.; Chambers, T. P.; Main, L. C.; Gastin, P. B. (Journal of Sports Science & Medicine, 2019)
This qualitative investigation sought to explore through a socio-cultural lens the perceived early training and competition environment, and support network of world-class Caribbean track and field athletes and the influence on their sport engagement and progression during early childhood and adolescence. Sixteen world-class track and field athletes (8 males and 8 females; M age = 29, SD = 5 years) from 6 English-speaking Caribbean islands took part in semi-structured interviews. A thematic analysis was performed on the transcribed data. Three superordinate themes were identified as key factors that influenced the early sporting development of world-class Caribbean athletes: (1) conducive sporting environment, (2) functional social support network, and (3) key organizational input. Findings revealed that perceived high levels of deliberate play activity in childhood (6 - 12 years) and an intense track and field competition culture in adolescence (13 - 20 years) were conducive to the continued engagement and progression of world-class Caribbean track and field athletes at the junior level. Furthermore, world-class athletes perceived themselves to be positively influenced by the support received from their immediate social support network and key organizations during this period. This study showed that a conducive sporting environment coupled with optimal social and organizational support may have encouraged world-class Caribbean athletes to remain engaged in track and field and to successfully progress within the sport at the junior level. Findings shed light on the sporting culture at the junior level within the Caribbean region and provide insight into key environmental factors that can influence and foster the development of future World Champions and Olympians. Key Points